The viability of coworking space as an alternative workspace - Tai, Rica Isabel Sia (College of Home Economics, University of the Philippines Diliman, 2015)
ABSTRACT The purpose of the study was to examine selected coworking spaces in Metro Manila in terms of their viability as alternative workspaces for independent professionals, entrepreneurs, and startup companies. The study employed an exploratory approach and utilized data gathering methods such as interview, survey, and visual documentation. To determine the five (5) participating companies, a quota sampling strategy was used thereafter, purposive sampling was employed to choose the five (5) informants of the study who were either the owners or managers of the coworking companies. For the survey, a total of forty-two (42) respondents comprised of coworking clients were selected through convenience sampling. The instrumentation for the study included an interview guide, an iPad voice recording application, a notebook and pen, a subject-completed survey questionnaire, and a cellphone camera. Results showed that coworking spaces are viable as alternative workspaces. The study revealed that people who worked in coworking spaces were productive whether they worked individually or in groups. The services and amenities differed for every company, depending on the size of the workspace and the unique needs of the community it served. The problems and issues of the coworking spaces were mostly operational, which can be addressed by increasing manpower and improving administrative tasks. Currently, Filipinos have not yet fully grasped and taken advantage of the full potential of coworking spaces. The coworking companies are still slowly trying to improve in order to build bigger communities and fully maximize the opportunities that lie in their user network.